PENGARUH PENGGUNAAN TEKNIK TIRU MODEL TERHADAP KETERAMPILAN MENULIS PUISI - Ramayani, Sri; Atmazaki, Atmazaki; Noveria, Ena (Universitas Negeri Padang, 2016)
ABSTRACT The purpose of the research is analyze the effect of the use of techniques to imitate the model of poetry writing skills of students of class VII SMP Negeri 3 Kota Solok. The data of this research is test result score of poetry writing skills for students at class VII SMP Negeri 3 Solok before using the technique to imitate the model and test result score of poetry writing skills for students at class VII SMP Negeri 3 Solok after using the technique to imitate the model. Data is collected by work method test.The result of this research is it has significance influence of techniques to imitate the model of poetry writing skills of students of class VII SMP Negeri 3 Solok at significant level of 95% with degrees of freedom (n–1), namely thitung > ttabel (7,52>1,72). H0 is refused and H1 is accepted because the result of hypothesis test going to show that thitung is bigger than ttabel. Kata kunci: Teknik Tiru Model, Keterampilan Menulis